Investigation of microtremors observed at historic masonry townhouse buildings after Nepal earthquake - Mukai, Yoichi; Hoshino, Hayato; Yamamoto, Naohiko; Masui, Masaya; Miyauchi, Anri; Suwal, Ram Prasad (Frontiers in Built Environment, 2022)
The Gorkha earthquake in 2015 was a recent large-scale earthquake that caused severe damage to many historic masonry buildings in the Kathmandu Valley, Nepal. The authors conducted a visual inspection survey of seismically damaged buildings after the earthquake in the historic town district of Bhaktapur in the Kathmandu Valley. The first part of this paper reports the distribution of the historic masonry buildings for each damage level in the surveyed area. A concentrating zone of severely-damaged buildings was explicitly found in the damage-level distribution map. Almost half of all the surveyed buildings were severely damaged during the earthquake, and most of these were historic masonry townhouse buildings. In the second part, the ambient vibration characteristics of the conventional historic masonry buildings in Bhaktapur are investigated. Typical dwelling houses in a historic town district in Nepal, which generally formed terraced houses built around a courtyard, were targeted for the measurement. Thus, the influence of adjacent buildings, which makes it difficult to identify the predominant natural frequencies from building vibration measurements, was also observed. Microtremor measurements using two accelerometers were conducted at 11 historic masonry buildings to investigate the discrimination degree for identifying the predominant natural frequency of conventional townhouse buildings. The estimated primary natural frequencies of these buildings were compared with the results of the screening model analysis. The advantages of using the proposed screening model analysis to improve the uncertainty of the first natural frequency identification by the microtremor measurement are discussed. Additional measurements of the microtremors at 4 of the 11 measured buildings were conducted using a different location combination of the two acceleration sensors. The sensors were placed between two different floors, and the transfer functions of each floor were investigated to observe the predominant vibration components on the floors in the entire building. Moreover, the coherence values observing the in-plane correlation of the floor responses were also analyzed for the dataset measured at two points separated on the same floor. Finally, an effective method for measuring the microtremors is discussed to improve the assessment of the vibration characteristics of conventional historic masonry buildings in Nepal.